Amplitude analysis of B±→[pi]± K+K− decays - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2019)
The first amplitude analysis of the $B^± → π^± K^+ K^-$ decay is reported based on a data sample corresponding to an integrated luminosity of 3.0 fb$^{-1}$ of $pp$ collisions recorded in 2011 and 2012 with the LHCb detector. The data is found to be best described by a coherent sum of five resonant structures plus a nonresonant component and a contribution from $ππ \leftrightarrow KK$ $S$-wave rescattering. The dominant contributions in the $π^± K^\mp$ and $K^{+}K^{-}$ systems are the nonresonant and the $B^± → ρ(1450)^{0}π^{±}$ amplitudes, respectively, with fit fractions around $30%$. For the rescattering contribution, a sizeable fit fraction is observed. This component has the largest $CP$ asymmetry reported to date for a single amplitude of $(-66 ± 4 ± 2)%$, where the first uncertainty is statistical and the second systematic. No significant $CP$ violation is observed in the other contributions.
Gesehen am 19.03.2020
Im Titel sind "±", "plus" und "minus" hochgestellt
*LHCb Collaboration: R. Aaij [und 844 weitere Personen]